Obesity and Diabetes in New York City, 2002 and 2004 - Shadi Chamany, MD, MPH; Donna Eisenhower, PhD; Thomas R. Frieden, MD, MPH; Gretchen Van Wye, PhD; Bonnie D. Kerker, PhD, MPH; Thomas Matte, MD, MPH; Lorna Thorpe, PhD, MPH (Centers for Disease Control and Prevention, 2008)
Introduction Obesity and diabetes have increased rapidly nationwide, yet reliable information on these disease trends in local urban settings is unavailable. We undertook this study to characterize trends in obesity and diagnosed diabetes from 2002 to 2004 among white, black, and Hispanic adult residents of New York City.Methods We used data from the Community Health Survey, an annual random-digit-dial telephone survey of approximately 10,000 New York City adults aged 18 years or older, and from the Behavioral Risk Factor Surveillance System, a similar nationwide survey. Main outcome measures were body mass index (BMI), calculated from self-reported height and weight, and self-reported diabetes.Results In 2 years, the prevalence of obesity increased 17% in New York City, from 19.5% in 2002 to 22.8% in 2004 (P < .0001). The prevalence of diagnosed diabetes also increased 17%, from 8.1% in 2002 to 9.5% in 2004 (P < .01). Nationally, the prevalence of obesity increased by 6% during this same time period (P < .05), and diabetes prevalence did not increase significantly. The median BMI among white adults in New York City was 25.1 kg/m2, significantly lower than among Hispanics (26.4 kg/m2) and blacks (26.6 kg/m2, P < .05). The prevalence of diabetes increased across all BMI categories.Discussion The rapid increase in obesity and diabetes in New York City suggests the severity of these twin epidemics and the importance of collecting and analyzing local data for local programming and policy making.